Hubungan Antara Kepedulian Terhadap Lingkungan dengan Perilaku Menyisakan Makanan pada Konsumen Angkringan X di Yogyakarta - Sri Ayu; Arundati Shinta; Femmy Lekahena (Jurnal Psikologi, 2026)
This research aims to determine the relationship between concern for the environment and the behavior of leaving food among angkringan consumers. There are two hypotheses proposed, namely: the first hypothesis is that there is a negative relationship between concern for the environment and food waste behavior. The second hypothesis is that there is a negative relationship between concern for the environment and the behavior of the amount of food waste produced. The research method used in this research is a quantitative method, with research subjects being 100 angkringan X consumers with the criteria for consumers who eat at angkringan, status (student or employee). Data collection was carried out by modifying the food waste behavior scale which has a reliability figure of 0.718 and a scale for the amount of waste produced. Meanwhile, the environmental concern scale has a reliability figure of 0.910. The data that has been analyzed shows that there is a negative relationship between concern for the environment and behavior of leaving food (r = -0.348, p = 0.000) and an effective contribution of 12.1%, the first hypothesis is accepted. Furthermore, the results show that there is a negative relationship between concern for the environment and the behavior of the amount of food waste produced (r = -0.300, p = 0.001) and an effective contribution of 9%, the second hypothesis is accepted.